Cardiovascular disease burden due to productivity losses in European Society of Cardiology countries - Luengo-Fernandez, R; Little, M; Gray, A; Torbica, A; Maggioni, AP; Huculeci, R; Timmis, AD; Vardas, P; Leal, J (Oxford University Press, 2023)
Objective Cardiovascular disease (CVD) is the leading cause of death across Europe. We estimated lost earnings (productivity losses) associated with premature mortality due to CVD, and separately for its main sub-categories of coronary heart disease and cerebrovascular disease, across 54 country members of the European Society of Cardiology (ESC).